2017
DOI: 10.1002/eat.22696
|View full text |Cite
|
Sign up to set email alerts
|

Validity and utility of the DSM‐5 severity specifier for binge‐eating disorder

Abstract: The findings provide support for the severity specifier for BED introduced in the DSM-5 as a means of addressing within-group variability in severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 33 publications
9
59
0
Order By: Relevance
“…Among studies that have examined the validity of the BN severity specifier (i.e., frequency of inappropriate compensatory behaviors), there is some evidence of concurrent validity, suggesting that severity specifiers are related to levels of ED and non-ED psychopathology in clinical and nonclinical samples (Dakanalis, Clerici, Riva, & Clerici, 2017; Grilo, Ivezaj, & White, 2015a; Jenkins, Luck, Cardy, & Staniford, 2016). Consistent with BN findings, clinical and nonclinical studies of BED have found differences in ED psychopathology and health status across DSM-5 severity groups, though there is inconsistent evidence for differences in depression (Grilo, Ivezaj, & White, 2015b, 2015c; Sysko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among studies that have examined the validity of the BN severity specifier (i.e., frequency of inappropriate compensatory behaviors), there is some evidence of concurrent validity, suggesting that severity specifiers are related to levels of ED and non-ED psychopathology in clinical and nonclinical samples (Dakanalis, Clerici, Riva, & Clerici, 2017; Grilo, Ivezaj, & White, 2015a; Jenkins, Luck, Cardy, & Staniford, 2016). Consistent with BN findings, clinical and nonclinical studies of BED have found differences in ED psychopathology and health status across DSM-5 severity groups, though there is inconsistent evidence for differences in depression (Grilo, Ivezaj, & White, 2015b, 2015c; Sysko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Delineating the determinants of distress and role functioning impairment may also assist in the refinement of the diagnostic criteria of this relatively new In regards to binge-eating frequency, studies have consistently found that binge eating on an at-least weekly basis is associated with significant psychosocial impairment (e.g., Mitchison, Hay, Slewa-Younan, & Mond, 2012), although greater binge-eating frequency may be associated with higher levels of distress and disability and poorer treatment outcomes (Dakanalis, Colmegna, Riva, & Clerici, 2017). Delineating the determinants of distress and role functioning impairment may also assist in the refinement of the diagnostic criteria of this relatively new In regards to binge-eating frequency, studies have consistently found that binge eating on an at-least weekly basis is associated with significant psychosocial impairment (e.g., Mitchison, Hay, Slewa-Younan, & Mond, 2012), although greater binge-eating frequency may be associated with higher levels of distress and disability and poorer treatment outcomes (Dakanalis, Colmegna, Riva, & Clerici, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Differences across EWD conditions also seem to exist, with the current evidence revealing that perfectionism and fear of criticism are more recurrent in AN-r, whereas affective instability and emotional dysregulation are more evidenced in AN-bp and BN [13]. Although research on BED (recently recognized as a distinct diagnostic category in the DSM-5) is still limited [13], some studies suggested that (obese and nonobese) patients with BED endorse comparable levels of affective instability to those with BN [2,17,18], and indicated that this variable predicts BED and BN severity [17,18]. Impulsiveness, however, appears to be a key predictor for overweight and obesity development [12].…”
Section: Personality and Eating And Weight Disorders: The State Of Thmentioning
confidence: 78%